Case Report: Capillary Leak Syndrome With Kidney Transplant Failure Following Autologous Mesenchymal Stem Cell Therapy - Večerić-Haler, Željka; Kojc, Nika; Sever, Matjaž; Zver, Samo; Švajger, Urban; Poženel, Primož; Hartman, Katrina; Urdih, Tereza; Mlinšek, Gregor; Oblak, Manca; Aleš Rigler, Andreja; Ihan, Alojz; et al. (Frontiers in Medicine, 2021)
Mesenchymal stem cells (MSCs) have attracted great interest in the field of kidney transplantation due to their immunomodulatory and reparative properties. In registered clinical trials, MSCs have been used before, at the time of, or early after transplantation and have been reported to be well-tolerated with no serious safety concerns. No results are available on the use of MSCs in the late post-transplant period. Here, we present a case report of a severe systemic complication mimicking capillary leak syndrome with ultimate kidney transplant failure after autologous transplantation of MSCs used as rescue treatment of late antibody-mediated kidney allograft rejection.